Characterization and phylogenetic analysis of the complete mitochondrial genome of Notostomum cyclostomum - Jun Young Chae; Jin Ho Kim; Tae-Wook Kang; Hyung-Ho Lee; Moo-Sang Kim (Mitochondrial DNA Part B, 2022)
Notostomum cyclostomum is a parasite that lays eggs on the snow crab shells and causes various diseases by parasitizing fish. Although there have been some studies on the life history of this parasite and the associated fish diseases, little is known about the molecular biology of this parasite. Thus, here we report the mitochondrial genome of N. cyclostomum, which is 16,972 bp long and contains 13 mitochondrial protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a putative control region with a 92% AT-rich sequences between tRNA-R and tRNA-H. Phylogenetic analysis using 13 PCGs confirmed that N. cyclostoum belongs to the family Pisciodlidae. This is the first study revealing the complete mitochondrial genome sequence of N. cyclostomum.